2019
DOI: 10.4103/jfmpc.jfmpc_676_19
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and preferences regarding sex and contraception, amongst adolescents

Abstract: Introduction:Conceptually and by the outlook, the reproductive and sexual health needs of adolescents differ from those of adults. Adolescent girls are coerced into unwanted sex or marriage, putting them at risk of unwanted pregnancies, unsafe abortions, sexually transmitted infections (STIs) including HIV, and dangerous childbirth. A majority of young people do not have correct information on the use of contraceptives or the prevention of pregnancy and STIs, and youth-friendly reproductive health services are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Trikha [ 44 ] found the initiation of sexual intercourse among students aged between 14 and 19 years. One article reported that the preference for sexual intercourse among adolescent girls was between the ages of 15 and 19 years [ 43 ]. The age gap between sexual contact and sexual intercourse was discussed in one study (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trikha [ 44 ] found the initiation of sexual intercourse among students aged between 14 and 19 years. One article reported that the preference for sexual intercourse among adolescent girls was between the ages of 15 and 19 years [ 43 ]. The age gap between sexual contact and sexual intercourse was discussed in one study (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Seven articles described the understanding of contraception among adolescent girls between 15 and 19 years [ 36 , 41 , 48 , 54 , 58 – 61 ]. Female sterilisation, male sterilisation, Intra Uterine Devices, Copper-T, I-pill, and condoms were the major contraceptives explained by teenage girls [ 35 , 36 , 59 ] but the understanding regarding condoms, oral pills, and emergency contraceptives was described in some of the articles [ 43 , 60 – 63 ]. Knowledge about abortion among adolescent girls was explained in four articles [ 35 , 40 , 59 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten out of 37 articles focused on adolescent girls and young women, while the rest considered women in the reproductive age group (15–49) as the study sample. These studies were conducted in Delhi [ 33 , 34 ], Maharashtra, Gujarat [ 35 ], Uttar Pradesh [ 36 ], Bihar [ 37 ] Punjab [ 38 ], Tamil Nadu [ 39 ] using primary data. At the same time, Tripathy [ 40 ] used DLHS data at the all-India level for this age group to analyze the awareness about sexual and reproductive needs.…”
Section: Resultsmentioning
confidence: 99%
“…There is a significant association between the nuclear status of a family and preference for premarital sex [ 38 ]. Education and economic status are significant determinants of pre and extramarital sex of married men.…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 17 ] are among factors affecting divorce, especially among newly married couples. [ 18 19 ] The best tool to achieve a desirable sexual Function is education and creating a positive attitude towards sexual matters. [ 20 21 ] Sex education is one of the priorities of women's health[ 22 ] and has been heralded as effective in promoting sexually healthy behavior in youth.…”
Section: Introductionmentioning
confidence: 99%